Trends of Mycobacterium bovis Isolation and First-Line Anti-tuberculosis Drug Susceptibility Profile: A Fifteen-Year Laboratory-Based Surveillance. - Miriam Bobadilla-del Valle; Pedro Torres-González; Miguel Enrique Cervera-Hernández; Areli Martínez-Gamboa; Brenda Crabtree-Ramirez; Bárbara Chávez-Mazari; Narciso Ortiz-Conchi; Luis Rodríguez-Cruz; Axel Cervantes-Sánchez; Tomasa Gudiño-Enríquez; Carmen Cinta-Severo; José Sifuentes-Osornio; et al. (PLoS Neglected Tropical Diseases, 2015)
Mycobacterium tuberculosis causes the majority of tuberculosis (TB) cases in humans; however, in developing countries, human TB caused by M. bovis may be frequent but undetected. Human TB caused by M. bovis is considered a zoonosis; transmission is mainly through consumption of unpasteurized dairy products, and it is less frequently attributed to animal-to-human or human-to-human contact. We describe the trends of M. bovis isolation from human samples and first-line drug susceptibility during a 15-year period in a referral laboratory located in a tertiary care hospital in Mexico City.Data on mycobacterial isolates from human clinical samples were retrieved from the laboratory's database for the 2000-2014 period. Susceptibility to first-line drugs: rifampin, isoniazid, streptomycin (STR) and ethambutol was determined. We identified 1,165 isolates, 73.7% were M. tuberculosis and 26.2%, M. bovis. Among pulmonary samples, 16.6% were M. bovis. The proportion of M. bovis isolates significantly increased from 7.8% in 2000 to 28.4% in 2014 (X(2)trend, p<0.001). Primary STR resistance was higher among M. bovis compared with M. tuberculosis isolates (10.9% vs.3.4%, p<0.001). Secondary multidrug resistance (MDR) rates were 38.5% and 34.4% for M. bovis and M. tuberculosis, respectively (p = 0.637). A rising trend of primary STR monoresistance was observed for both species (3.4% in 2000-2004 vs. 7.6% in 2010-2014; p = 0.02).There is a high prevalence and a rising trend of M. bovis isolates in our region. The proportion of pulmonary M. bovis isolates is higher than in previous reports. Additionally, we report high rates of primary anti-tuberculosis resistance and secondary MDR in both M. tuberculosis and M. bovis. This is one of the largest reports on drug susceptibility of M. bovis from human samples and shows a significant proportion of first-line anti-tuberculosis drug resistance.